PENGARUH TEKNIK RELAKSASI GUIDED IMAGERY TERHADAP KUALITAS TIDUR PADA LANSIA DI UPT PELAYANAN SOSIAL LANSIA BINJAI - Indra P P; Linda F Tampubolon; Samani Ndruru (STIKes Santa Elisabeth Medan, 2019)
Complaints about night-time sleep difficulties often occur among the elderly. Difficulties in sleep that affect the quality of sleep of elderly are still many elderly people often have woke up.Guided imageryis a non farmokologi therapy is often used to treat sleep disorders andcan is useful to reduce anxiety, pain and facilitate good sleep quality. Goals : This study aimed to determine the effect of guided imagery relaxation technique on quality of sleep in the elderly in social services UPT Elderly Binjai. Method : This research method using one-group pre-post test design test. The sampling technique is purposive sampling, with a sample of 20 respondents. Measuring instruments used PSQI questionnaire. Result : Analysis of the data shows the results of the sleep quality pre-test all elderly experience poor sleep quality (100%) and post-test were experiencing good sleep quality as much (10%) and poor sleep quality as much (90%). The results showed that guided imagery relaxation techniques affect the quality of sleep in elderly UPT Elderly Social services Binjai p = 0.001 (<0.05). Conculsion : Researchers suggest to the elderly in order to continue the selfguided imagery regularly.